2002
DOI: 10.1095/biolreprod.102.006171
|View full text |Cite
|
Sign up to set email alerts
|

Improving Delivery and Offspring Viability of In Vitro-Produced and Cloned Sheep Embryos1

Abstract: Recently developed, assisted reproductive technologies (e.g., in vitro embryo production and nuclear transfer) have encountered perinatal morbidity/mortality of the offspring produced, which are likely to hinder the application of these techniques. Consequently we have sought to develop a system of hormonal stimulation that will ensure the delivery of offspring more prepared for extrauterine life. Here we examine deliveries outcome in sheep carrying in vitro-produced and nuclear transfer (NT) embryos in compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 48 publications
(69 reference statements)
0
34
0
1
Order By: Relevance
“…Due to the large size of a proportion of the lambs and associated birthing difficulties and ewe and lamb mortality experienced during the lambing of recipient crossbred ewes in ET Trial 1, a combination of 5 ml dexame thasone (Dexadreson 2 mg/ml; Intervet) and 5 ml oestradiol benzoate (Mesalin 0.2 mg/ml; Intervet) was given at Day 143 of gestation to each of the Merino recipient ewes in ET Trial 2 to induce earlier births and smaller offspring (Ptak et al 2002).…”
Section: Lambingmentioning
confidence: 99%
“…Due to the large size of a proportion of the lambs and associated birthing difficulties and ewe and lamb mortality experienced during the lambing of recipient crossbred ewes in ET Trial 1, a combination of 5 ml dexame thasone (Dexadreson 2 mg/ml; Intervet) and 5 ml oestradiol benzoate (Mesalin 0.2 mg/ml; Intervet) was given at Day 143 of gestation to each of the Merino recipient ewes in ET Trial 2 to induce earlier births and smaller offspring (Ptak et al 2002).…”
Section: Lambingmentioning
confidence: 99%
“…Thus, maintaining an optimal level of ROS by adding antioxidants to the culture media seems to be absolutely essential for the proper production of gametes, successful interaction of gametes, fertilisation and development of embryos in vitro (Miesel et al, 1993;Sanocka and Kurpisz, 2004). Some authors have reported improvements in the overall outcome of IVF-IVEC -embryo transfer procedure (Ptak et al, 2002). Others have attempted to supplement the culture media with different sets of nutrients or co-culture the oocytes and embryos to obtain better results (Rexroad and Powell, 1993;Urdaneta et al, 2003;Karja et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Oocytes having at least 2-3 layers of compact cumulus cells were selected for IVM in bicarbonate-buffered TCM-199 (Gibco) containing 2 mM glutamine, 0.3 mM sodium pyruvate, 100 μM cysteamine, 10 % fetal bovine serum (FBS) (Gibco), 5 μg/ml follicle stimulating hormone FSH (Ovagen, ICP, Auckland, New Zealand), 5 μg/ml luteinizing hormone (LH), and 1 μg/ml estradiol. Maturation was conducted in 4-well culture plates (Nunclon, Roskilde, Denmark) containing 0.4 ml/well of IVM medium, incubated in a humidified atmosphere of 5 % CO 2 in air at 38.5°C for 24 h [24]. After IVM, only selected MII oocytes with expanded cumulus and normal morphology were used for ICSI.…”
Section: Oocyte Recovery and In Vitro Maturation (Ivm)mentioning
confidence: 99%
“…All nuclei were counterstained with propidium iodide. Scale bar = 10 μm Fertilization was carried out at a final concentration of 5 × 10 6 spermatozoa/ml and left overnight in a humidified atmosphere at 38.5°C, 5 % CO 2 , and 7 % O 2 [24].…”
Section: In Vitro Fertilization (Ivf)mentioning
confidence: 99%
See 1 more Smart Citation